Effect of Pressure on Expanded Polystyrene (EPS) Dry Mix Mortar Block - Rosseira, Adrina; Anua Mohd Dahari, Syamsul; Kamaruddin, Kartini; Mat Zain, Mazni; Faliq Puaad, Bazli (International Journal of Engineering and Technology, 2018)
Nowadays, there is more demand than supply on the uses of material in the construction. Thus, the need to use alternative materials should be widely used and practiced among the construction and development to pro-longed the material for future generation supply. The objective of this study is to investigate the effect of different pressure exerted between 700 kPa, 900 kPa and 1100 kPa to the replacement of Expanded Polystyrene (EPS) at 20 %, 25 %, 30 %, 35 % and 40 % of sand replacement in achieving target strength of 5 N/mm² to 7 N/mm² of EPS dry mix mortar block. The tests were conducted at 7 and 28 days of curing with various replacements of EPS in the dry mix Besides, the study is also to identify the density of EPS Dry Mix Mortar Block due to pressure exerted (700 kPa, 900 kPa and 1100 kPa) as a lightweight block. From the result that obtained, it was found that the most suitable pressure to be exerted is 700 kPa since it was the less required pressure needed to achieve the target strength of 5-7 N/mm² at 20 % of EPS replacement which is 5.74 N/mm². Besides, it was shown that the increase of pressure exerted to the EPS dry mix mortar block also will increased its density thus resulted in higher compressive strength.